Taxonomy and evolutionary studies on the genus Psoralea L. (Psoraleeae, Fabaceae) - Bello, Abubakar (Department of Biological Sciences, 2017)
Psoraleeae is a tribe of the papilionoid legumes in Fabaceae comprising ca. 223 species in nine genera. Members of Psoraleeae are distributed worldwide, though they mainly occur in the temperate biomes. Of these, ca. 60% of the species (mostly in Otholobium and Psoralea) are endemic to southern Africa predominantly in the Greater Cape Floristic Region (GCFR). The genus Psoralea, consisting of 75 species endemic to southern Africa, is the second most speciose legume in the GCFR after Aspalathus (280 species). This thesis, consisting of a literature review, three research chapters and synthesis, studies the taxonomy, evolutionary history and biogeography of Psoraleeae with an emphasis on Psoralea.